Biophytum sensitivum : Ancient medicine, modern targets - K M Sakthivel; C Guruvayoorappan (Wolters Kluwer Medknow Publications, 2012)
Research on medicinal plants began to focus on discovery of natural products as potential active principles against various diseases. Medicinal plants are very interesting, have the ability to produce remarkable chemical structures with diverse biological activities. Biophytum sensitivum is used as traditional medicine to cure variety of diseases. During the last few decades, extensive research has been carried out to elucidate the chemistry, biological activities, and medicinal applications of B. sensitivum. Phytochemical analysis have shown that the plant parts are rich in various beneficial compounds which include amentoflavone, cupressuflavone, and isoorientin. Extracts and its bioactive compounds have been known to possess antibacterial, anti-inflammatory, antioxidant, antitumor, radioprotective, chemoprotective, antimetastatic, antiangiogenesis, wound-healing, immunomodulation, anti-diabetic, and cardioprotective activity. The present review has been carried out to shed light on the diverse role of this plant in the management of various ailments facing us.